Diffusing capacity of lungs for carbon monoxide associated with subclinical myocardial impairment in systemic sclerosis: A cardiac MR study - Xiaofeng Zeng; Qian Wang; Dong Xu; Xihai Zhao; Yuhua Wang; Jiaxin Zhou; Huilin He; Xinyu Tong; Zihan Ning; Chenlin Du; Zuo-Xiang He (RMD Open, 2023)
Background Systemic sclerosis (SSc) is characterised by microvascular and fibrotic lesions, which are located not only in skin but also in lungs and heart.Objective This study aimed to investigate the association between lung function and myocardial T1 values using cardiac MR (CMR) imaging in patients with SSc without cardiovascular symptoms.Methods The SSc patients and age- and sex-matched healthy subjects underwent CMR. The cardiac function and native T1 values of myocardium and lung function were measured. Spearman’s rank correlations and linear regression analyses were performed to determine the association between lung function and myocardial T1.Results Forty-five SSc patients (aged 47.7±13.2 years, 40 females) and 23 (aged 46.0±14.4 years, 20 females) healthy subjects were enrolled. SSc patients exhibited considerably higher native T1 values compared with healthy subjects (1305.9±49.8 ms vs 1272.6±37.6 ms, p=0.006). Linear regression analysis revealed that decrease of diffusing capacity of lungs for carbon monoxide (DLCO) in SSc patients was notably associated with myocardial native T1 value before (β –1.017; 95% CI –1.883 to –0.151; p=0.022) and after adjusting for confounding factors (β –1.108; 95% CI −2.053 to –0.164; p=0.023). Moderate-to-severe decrease of DLCO was found to be significantly associated with myocardial native T1 value (β 48.006; 95% CI 17.822 to 78.190; p=0.003) after adjusting for confounding factors.Conclusion DLCO inversely correlates with myocardial native T1 values in SSc patients, particularly moderate-to-severely decreased DLCO, suggesting that DLCO might be a potential indicator for subclinical myocardial impairment in SSc patients.